Global nonexistence of solutions for Caputo fractional differential inequality with singular potential term. Issue 5 (4th May 2022) - Khirani, Moustafa; Tellab, Brahim; Haouam, Kamel; Zennir, Khaled
Abstract: This paper is reserved to discuss the existence of a critical exponent of Fujita type for a class of homogeneous Caputo fractional diﬀerential inequality with a singular term by using the test function method, to extend the result of global nonexistence of solutions obtained by Xiao and Fang in [12].